Clinico-pathological review of ciliated muconodular papillary tumour of lung - Dr. Sabah Nayef Nemri; Dr. Nazima Haider; Fatima, Sohaila (Tropical Journal of Pathology and Microbiology, 2018)
Pulmonary tumours with cilia formation are rare and are usually recognized as benign. Ciliated muconodular papillary tumour (CMPT) of lung is a rare entity recently described in 2002. It is characterized by the presence of papillary tumour consisting of ciliated columnar, goblet, and basal cells. Although most of its features are of a benign tumour, some histological characteristics do suggest low-grade malignancy. We describe a case of CPMT in a 36 year old male.